Fat and carbohydrate metabolism during submaximal exercise in children - Aucouturier, J.; Baker, J.; Duche, P. (Sports Medicine, 2008)
During exercise, the contribution of fat and carbohydrate to energy expenditure is largely modulated by the intensity of exercise. Age, a short- or long-term diet enriched in carbohydrate or fat substrate stores, training and gender are other factors that have also been found to affect this balance. These factors have been extensively studied in adults from the perspective of improving performance in athletes, or from a health perspective in people with diseases. During the last decade, lifestyle changes associated with high-energy diets rich in lipid and reduced physical activity have contributed to the increase in childhood obesity. This lifestyle change has emerged as a serious health problem favouring the early development of cardiovascular diseases, insulin resistance or type 2 diabetes mellitus. Increasing physical activity levels in young people is important to increase energy expenditure and promote muscle oxidative capacity. Therefore, it is surprising that the regulation of balance between carbohydrate and lipid use during exercise has received much less attention in children than in adults. In this review, we have focused on the factors that affect carbohydrate and lipid metabolism during exercise and have identified areas that may be relevant in explaining the higher contribution of lipid to energy expenditure in children when compared with adults. Low muscle glycogen content is possibly associated with a low activity of glycolytic enzymes and high oxidative capacity, while lower levels of sympathoadrenal hormones are likely to favour lipid metabolism in children. Changes in energetic metabolism occurring during adolescence are also dependent on pubertal events with an increase in testosterone in boys and estrogen and progesterone in girls. The profound effects of ovarian hormones on carbohydrate and fat metabolism along with their effects on oxidative enzymes could explain that differences in substrate metabolism have not always been observed between girls and women. Finally, although the regulatory mechanisms of fat and carbohydrate balance during exercise are quite well identified, there are a lack of data specific to children and most of the evidences reported in this review were drawn from studies in adults. Isotope tracer techniques and nuclear magnetic resonance will allow non-invasive investigation of the metabolism of the different substrate sources in skeletal muscle.